Nikah Mut'ah Dalam Kitab Tafsir Al-Qur'an - Muhammad, Muhammad (Musawa Jurnal Studi Gender dan Islam, 2002)
Mut'ah marriage, as a temporary married, was once permitted by the Prophet in the context of war. In the latter period of his apostolacy, the Prophet Muhammad prohibited it. Both the permission and prohibition of this mut' ah marriage are to be found within the realm of the hadith, and differences of opinion about their validity may arise. Meanwhile there is no verse in the al-Qur'an that specifically refers to this concept of mut'ah marriage. Nevertheless the majority of commentators touch on the issue of mut'eh marriage when faced with QS. al-Nisa (4): 24. Through this paper, the Prophet attempts to expose the opinions of a number of commentators on these verses concerning mut'ah marriage. Most commentators view it as something forbidden, in accordance with the prohibition made by the Prophet late in his life.